Defiance in Manchuria : - Ogata, Sadako N. (University of California Press, 1964)
The author explores the question of why Japan followed an expansionist foreign policy that worked to her own destruction. He has chosen to examine the Manchurian Affair of 1931 because it marks the beginning of Japan's uncontrolled expansion on the Asian continent, and also because "here are found the origins of later maladies."